Naturalness in the Spanish Dubbing Language: a Case of Not-so-close Friends - Fresco, Pablo (Meta, 2009)
AbstractThe present article examines the Spanish dubbing language from the point of view of its naturalness. The premise is that dubbing language is best analyzed by comparing it to the register it imitates, as long as its peculiar features are taken into consideration. This study is divided into two parts: firstly, a description of the features that make dubbing dialogue different from real dialogue, focusing on those arising from the source text; secondly, a comparative analysis of dubbed and real dialogue. In the latter, a corpus of spontaneous conversations will be used as a yardstick for natural dialogue and the main strategies used in colloquial conversation will provide the linguistic units to be analyzed: intensifiers and discourse markers. The main unidiomatic features detected are the use of anglicisms, especially at the pragmatic level, and a certain shift in tone that may cause a variation in the relation among the participants in the dubbed text. Finally, the notion of suspension of linguistic disbelief is put forward as a possible explanation for the perpetuation of unnatural features in dubbing language.